An Anatomical Study Of Femoral Sulcus Angle On Dry Bones: An Anatomical Study Of Femoral Sulcus Angle On Dry Bones - Priyangi M. Kathayat; Mandar K. Shah; Dr. Swati D. Shah (National Journal of Integrated Research in Medicine, 2020)
Background: The distal end of femur has immense importance from the anatomical, functional and clinical point of view. The femoral sulcus angle is formed by two lines joining the highest points on the medial and the lateral condyles which meet at the lowest point on the intracondylar groove of the femur. Aim: This study aims to determine the size of femoral sulcus angle in local population. Due to difficulty in the determination of the gender of the femur we have limited our study to left and right bones. Material and Methods: Attempts are made to measure the sulcus angle of the femora. Study was carried out in the anatomy department of Smt. NHL Municipal Medical College, Gujarat state. Total 150 dry femora were analyzed and statistical analysis was done by using appropriate software. The femora were placed in a supine position on a flat table and with a goniometer the measurement was performed. To avoid faulty measurement and error, all the femoral angles were calculated by a single researcher. Result: Our results show the mean value of sulcus angle in right femora is 143.625ï‚° and left is 143.39ï‚°. The standard deviation is 9.269ï‚° in right and 8.9919ï‚° in left femora. The result of unpaired t test is 0.7519. The p value is 0.98 which is insignificant. Conclusion: There is no significant difference in the value of sulcus angle between right and left femora. This study gives us an idea about the mean size of the femoral sulcus angle in population. [Kathayat P Natl J Integr Res Med, 2020; 11(2):60-63]